2014
DOI: 10.1177/0363546514536874
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Symptomatic Superior Labrum Anterior-Posterior Tears in Patients Older Than 40 Years

Abstract: While studies show that good outcomes can be obtained with SLAP repair in an older cohort of patients, age older than 40 years and workers' compensation status are independent risk factors for increased surgical complications. The cumulative evidence supports labral debridement or biceps tenotomy over labral repair when an associated rotator cuff injury is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…11,[14][15][16]18,19,21,23,30 There is conflicting evidence regarding the extent to which age-related degenerative and physiologic changes impact outcomes following surgical repair of other areas of the labrum. 24,31,32 Provencher et al 31 reported the relative risk of surgical failure following superior labrum anterior-posterior repair was 3.45 (95% confidence interval, 2.0-4.9) for patients older than 36 years. Another series describing arthroscopic repair of circumferential labral tears found no association between age and postoperative outcomes, complications, or revision rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[14][15][16]18,19,21,23,30 There is conflicting evidence regarding the extent to which age-related degenerative and physiologic changes impact outcomes following surgical repair of other areas of the labrum. 24,31,32 Provencher et al 31 reported the relative risk of surgical failure following superior labrum anterior-posterior repair was 3.45 (95% confidence interval, 2.0-4.9) for patients older than 36 years. Another series describing arthroscopic repair of circumferential labral tears found no association between age and postoperative outcomes, complications, or revision rates.…”
Section: Discussionmentioning
confidence: 99%
“…11,23 Differences in mechanism of injury, tissue healing capacity, and other age-related changes may result in inferior outcomes for middle-aged adults undergoing labral repair compared with younger overhead athletes. 24,25 The purpose of this study was to evaluate the clinical results of arthroscopic repair of posterior labral tears in patients 35 years and older using validated functional outcome measures, as well as to report the incidence of complications and revision procedures. It was hypothesized that these patients would have worse outcomes than those previously reported in their younger counterparts.…”
mentioning
confidence: 99%
“…1) Level 2*: (Gorantla et al, 2010) 2) Level 2*: (Erickson et al, 2015) Level 1: systematic review, level 2*: downgraded systematic review, level 2: randomized clinical trial (RCT) or inception cohort study, level 4: Case series or casecontrol study.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Type II lesions are the most common to be approached surgically. Repair may be performed in patients younger than 40 years, but in older patients, successful healing and favorable outcomes with repair are less predictable, and biceps tenodesis or tenotomy is more typically performed-particularly if there is a coexisting rotator cuff tear (46).…”
Section: Labral Repairmentioning
confidence: 99%